Assessment of droplet digital polymerase chain reaction for measuring BCR‐ABL1 in chronic myeloid leukaemia in an international interlaboratory study. (10th June 2021) - Scott, Stuart; Cartwright, Ashley; Francis, Sebastian; Whitby, Liam; Sanzone, A. Pia; Mulder, André; Galimberti, Sara; Dulucq, Stephanie; Mauté, Carole; Lauricella, Calogero; Salmon, Matthew; Rose, Susan; et al.
Summary: Measurement of BCR activator of RhoGEF and GTPase ‐ABL proto‐oncogene 1, non‐receptor tyrosine kinase ( BCR‐ABL1 ) mRNA levels by reverse transcription quantitative polymerase chain reaction (RTqPCR) has been critical to treatment protocols and clinical trials in chronic myeloid leukaemia; however, interlaboratory variation remains a significant issue. Reverse transcriptase droplet digital PCR (RTddPCR) has shown potential to improve testing but a large‐scale interlaboratory study is required to definitively establish this. In the present study, 10 BCR‐ABL1 ‐positive samples with levels ranging from molecular response (MR) 1·0 –MR 5·0 were tested by 23 laboratories using RTddPCR with the QXDX BCR‐ABL %IS kit. A subset of participants tested the samples using RTqPCR. All 23 participants using RTddPCR detected BCR‐ABL1 in all samples to MR 4·0 . Detection rates for deep‐response samples were 95·7% at MR 4·5, 78·3% at MR 4·7 and 87·0% at MR 5·0 . Interlaboratory coefficient of variation was indirectly proportional to BCR‐ABL1 level ranging from 29·3% to 69·0%. Linearity ranged from 0·9330 to 1·000 (average 0·9936). When results were compared for the 11 participants who performed both RTddPCR and RTqPCR, RTddPCR showed a similar limit of detection to RTqPCR with reduced interlaboratory variation and better assay linearity. The ability to detect deep responses with RTddPCR, matched with an improved linearity and reduced interlaboratory variation will allow improved patient management, and is of particular importance for future clinical trials focussed on achieving and maintaining treatment‐free remission.